Imprisoned bodies: Socio-education in an experience with dance in Cuiabá (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This article describes a dance workshop with young interns at the Centro de Atendimento Socioeducativo de Cuiabá (CASE-MT) and reflects on the strategies used to face a complex and conflicted situation. In the space of incarceration that has coercion at its core, how can one use the body in dance with incarcerated teenagers?
Keywords: Socio-education; Dance; Strategies